2014
DOI: 10.1093/inthealth/ihu074
|View full text |Cite
|
Sign up to set email alerts
|

Sociocultural factors perpetuating the practices of early marriage and childbirth in Sylhet District, Bangladesh

Abstract: Future efforts to promote delay in marriage and subsequent early childbearing should focus on allaying the fears of infertility related to delay in childbearing or secondary to contraceptive use, both for newly married couples and household decision-makers such as mothers-in-law.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 24 publications
3
42
0
Order By: Relevance
“…; Henry et al. ). Some men do not approve of contraception because they are concerned that it could encourage infidelity, challenge their own fertility preferences, or undermine their authority as heads of households (Watkins, Rutenberg, and Wilkinson ; Harrington et al.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…; Henry et al. ). Some men do not approve of contraception because they are concerned that it could encourage infidelity, challenge their own fertility preferences, or undermine their authority as heads of households (Watkins, Rutenberg, and Wilkinson ; Harrington et al.…”
mentioning
confidence: 98%
“…A number of qualitative studies suggest that many women who decide to use contraception secretly do so for serious reasons and could face dire consequences if their partners discover their contraceptive use. In many cultures women are expected to be obedient to their husbands, to conceive soon after marriage, and to be sexually available to their husbands (Wilson-Williams et al 2008;Henry et al 2015). Some men do not approve of Ifta Choiriyyah is doctoral student and Stan Becker is Professor, Department of Population, Family, and Reproductive Health, Johns Hopkins Bloomberg School of Public Health.…”
mentioning
confidence: 99%
“…The National Campaign to Prevent Teen Pregnancy of World Health Organization reported that career opportunity for many young women was reduced by earlier childbearing and failure to complete high school education [30]. Despite these obvious problems and undesirable consequences, most of the adolescent pregnancies in Bangladesh were pre-planned and highly valued [33]. With poverty and lack of education, the young families would not know the medical and health problems associated with their behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…1,5,6 Other causes of early marriage that have been identified include customs, gender discrimination, ignorance, peer group influence, and unexpected pregnancy, but the extent to which these affect different communities is not clear. 2,[9][10][11] It is noted for instance, in Bangladesh that the standard age-disparity between husband and wife is 8-10 years and families purposely seek for a much young woman for the son to marry. 10 Thus, where for instance a 25 years old man want to get married, the likelihood is that under-aged girl is the target.…”
Section: Introductionmentioning
confidence: 99%
“…2,[9][10][11] It is noted for instance, in Bangladesh that the standard age-disparity between husband and wife is 8-10 years and families purposely seek for a much young woman for the son to marry. 10 Thus, where for instance a 25 years old man want to get married, the likelihood is that under-aged girl is the target. Powerlessness is less articulated as a cause and this is exemplified in the story of 15 years old Kenyan girl Naisiae, who together with.…”
Section: Introductionmentioning
confidence: 99%